2021
DOI: 10.3803/enm.2021.101
|View full text |Cite
|
Sign up to set email alerts
|

The Genotype-Based Morphology of Aldosterone-Producing Adrenocortical Disorders and Their Association with Aging

Abstract: Primary aldosteronism (PA) is the most common cause of secondary hypertension, and is associated with an increased incidence of cardiovascular events. PA itself is clinically classified into the following two types: unilateral PA, mostly composed of aldosteroneproducing adenoma (APA); and bilateral hyperaldosteronism, consisting of multiple aldosterone-producing micronodules (APMs) and aldosterone-producing diffuse hyperplasia. Histopathologically, those disorders above are all composed of compact and clear ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
(117 reference statements)
0
6
0
Order By: Relevance
“…The less physiological aldosterone production is possibly due to the shrinkage of the ZG with decreased aldosterone synthase expression during aging, whereas the autonomous or renin-independent aldosterone production in older individuals is possibly due to the increased number of aldosterone-producing micronodules (APMs) [ 76 ]. Notably, APMs were reported to frequently harbor aldosterone-producing adenoma (APA) driving somatic mutations of various ion channels, including potassium inwardly rectifying channel subfamily J member 5 (KCNJ5) , calcium voltage-gated channel subunit alpha1 D (CACNA1D) , ATPase Na + /K + transporting subunit alpha 1 (ATP1A1) and ATPase plasma membrane Ca 2+ transporting 3 (ATP2B3) [ 11 , 12 ]. Another study also revealed the presence of numerous renin independent APMs in normal adrenal glands adjacent to APAs with autonomous aldosterone production [ 37 ].…”
Section: Age-related Changes In the Adrenal Cortexmentioning
confidence: 99%
See 3 more Smart Citations
“…The less physiological aldosterone production is possibly due to the shrinkage of the ZG with decreased aldosterone synthase expression during aging, whereas the autonomous or renin-independent aldosterone production in older individuals is possibly due to the increased number of aldosterone-producing micronodules (APMs) [ 76 ]. Notably, APMs were reported to frequently harbor aldosterone-producing adenoma (APA) driving somatic mutations of various ion channels, including potassium inwardly rectifying channel subfamily J member 5 (KCNJ5) , calcium voltage-gated channel subunit alpha1 D (CACNA1D) , ATPase Na + /K + transporting subunit alpha 1 (ATP1A1) and ATPase plasma membrane Ca 2+ transporting 3 (ATP2B3) [ 11 , 12 ]. Another study also revealed the presence of numerous renin independent APMs in normal adrenal glands adjacent to APAs with autonomous aldosterone production [ 37 ].…”
Section: Age-related Changes In the Adrenal Cortexmentioning
confidence: 99%
“…APA is the major cause of primary aldosteronism (PA), which accounts for 5–10% of all hypertensive patients [ 123 ]. The formation of APA is caused by somatic mutations of the aldosterone-driver gene, such as KCNJ5 , CACNA1D , ATP1A1 and ATP2B3 [ 12 ]. CPA is the result of abnormal differentiation from ZF cells and is usually caused by somatic mutations of protein kinase cAMP-activated catalytic subunit alpha ( PRKACA ) , GNAS complex locus ( GNAS ) and catenin beta 1 ( CTNNB1 ), resulting in hypercortisolism and clinical Cushing’s syndrome [ 106 ].…”
Section: Cellular Senescence In Normal Adrenal Cortex and Its Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…2 In a German cohort of PA, 77.6% of the patients had a positive result for at least one of three screening tests for Cushing's syndrome: a 1 mg overnight dexamethasone suppression test, late-night salivary cortisol and/or 24-h urinary free cortisol. 3 The coexistence of autonomous cortisol secretion was associated with poor clinical outcomes, impaired glucose metabolism and psychological symptoms in patients with PA. [3][4][5] With the development of monoclonal antibodies specific to steroidogenic enzymes, including CYP11B1 (11β-hydroxylase), CYP11B2 (aldosterone synthase) and CYP17A1 (17α-hydroxylase and 17,20-lyase), immunohistochemistry (IHC)-based analyses of adrenal tissues have provided new insights into the pathogenesis of PA. [6][7][8][9] CYP11B1 is expressed mainly in the adrenal zona fasciculata and is responsible for the synthesis of cortisol. The expression of CYP11B1 in adrenal adenoma tissue of patients with PA was positively associated with the excretion of glucocorticoid metabolites.…”
Section: Introductionmentioning
confidence: 99%